Susceptibility Antibiotics of Bacteria Causing Urinary Tract Infection in Pregnant Women Infected with COVID-19 - Hateet, Rashid Rahim (Kesmas, 2022)
Urinary tract infections (UTIs) are a significant issue in women of all ages, but they are especially common during pregnancy. Co-infection of the Coronavirus Disease 2019 (COVID-19) with UTIs in pregnant females is a hot topic today, as it may be linked to various conditions. Furthermore, understanding the types of bacteria that cause UTIs and related antimicrobial resistance may aid the clinician in selecting the appropriate empirical treatment. This study aimed to isolate and characterize causative agents of UTIs and determine antimicrobial treatment sensitivity patterns among pregnant women diagnosed with the COVID-19 admitted to Teaching Hospital X in Iraq. Antimicrobial drug resistance testing was performed on 42 mid-stream urine samples that had been prepared for culture. Escherichia coli (18/42.85%), Klebsiella pneumoniae (9/21.45%), Streptococcus galactica (7/16.66%), and Proteus mirabilis (4/9.52%) were the bacteria isolated and diagnosed from pregnant women. The infections Pseudomonas aeruginosa and Staphylococcus aureus were the least common (2/4.7). In conclusion, the isolated uro-pathogens showed high resistance to Gentamicin, Cefuroxime, Ceftriaxone and sensitive to Ampicillin and Nitrofurantoin. The common cause of UTIs among pregnant women infected with the COVID-19 was discovered to be Escherichia coli. Before recommending therapy, culture and sensitivity testing of isolates from urine tests should be conducted on a regular basis.